German mammography screening program: adherence, characteristics of (non-)participants and utilization of non-screening mammography-a longitudinal analysis - Miriam Heinig; Wiebke Schäfer; Ingo Langner; Hajo Zeeb; Ulrike Haug (BMC, 2023)
Abstract Background In Germany, all women aged 50-69 have been invited to biennial mammography screening since 2009. We aimed to assess longitudinal adherence over ten years in women aged 50 in 2009 and characterize the different adherence groups. Methods Using the German Pharmacoepidemiological Research Database (GePaRD, ~ 20% of the German population), we included women aged 50 in 2009 (baseline) with continuous health insurance coverage and without breast cancer or in-situ-carcinoma. We followed them until age 59 and categorized them according to mammography screening participation into the following groups: never, 1-2, 3-4, 5-6 times. We characterized these groups, inter alia, regarding the use of other preventive measures, non-screening mammography (i.e., mammography outside the organized screening program) and menopausal hormone therapy. Results Overall, 82,666 women were included. Of these, 27.6% never participated in the screening program, 15.1% participated 1-2 times, 31.7% participated 3-4 times and 25.6% participated regularly (5-6 times). Among regular participants, 91% utilized other preventive measures (e.g., cervical cancer screening, general health checkup) before baseline as compared to 66% among non-participants. Menopausal hormone therapy was least common among non-participants (11% vs. 18% among regular participants). Among non-participants, the proportions using ≥ 1, ≥ 2, and ≥ 3 non-screening mammographies between age 50-59 were 25%, 18%, and 15%, respectively. Conclusions Using a large cohort based on claims data, this study provides novel insights into longitudinal adherence to the mammography screening program and the use of mammography outside of the program in Germany. Between age 50-59, 57% of eligible women participated at least three times in the German mammography screening program and 28% (~ 3 in 10 women) never participated. Among non-participants, 15% had at least three non-screening mammographies during this period, indicating potential gray screening. Participants more often utilized other preventive measures as compared to non-participants.